Childhood craniopharyngioma: 20‐year institutional experience in Western Australia. Issue 5 (5th April 2013) - Rath, Shoshana R; Lee, Sharon; Kotecha, Rishi S; Taylor, Mandy; Junckerstorff, Reimar C; Choong, Catherine SY
<x xml:space="preserve">Abstract</x> Aim A retrospective audit was undertaken to evaluate modes of presentation and treatment outcomes for craniopharyngioma in a single paediatric institution over a 20‐year period. Methods A search of the neurosurgical and histopathological databases for patients under 21 years of age treated for craniopharyngioma between 1990 and 2010 was performed at our institution. The clinical records of eligible patients were reviewed and information regarding presentation, medical and surgical management and post‐treatment outcome were extracted and collated. Results Of 10 evaluable patients, the commonest presenting symptoms were headache and visual impairment. Clinical and biochemical evaluation undertaken prior to surgery revealed visual dysfunction in 70% and pituitary deficit in 30%. Gross total resection was achieved in 40% but was curative in only 20%. The remaining 80% required further surgical and/or radiotherapeutic intervention. Seven patients had radiation therapy with stabilisation in 70%. Multiple Pituitary Hormone Deficiency evolved in all patients over time, while visual impairment worsened in 30% post‐operatively and improved in 20%. Obesity was present in 50% after a mean follow‐up interval of 5.6 years and was apparent within 1 year of initial surgery in 30%. Although neurocognitive, psychological and behavioural problems were noted for some patients during medical review, only 20% of patients were formally assessed. Conclusions Craniopharyngioma is associated with significant long‐term morbidity. Attention to an integrated care pathway that includes standardised neurocognitive and psychological and behavioural assessment would facilitate early appropriate intervention and support leading to an improved quality of life for children with craniopharyngioma.